Conceptual maps in the understanding of the meaningful learning of the contents of Probability - Ribeiro, Naiara Aparecida (2018)
The purpose of this article is to present the results of an investigation carried out with high school students regarding the content of probability, supported by the perspective of meaningful learning theory. For the development of the research was used a previous organizer for the teaching of probability and concept maps for the analysis of the students' knowledge, based on the elements that define the learning as meaningful present in the constructions realized by the students. The research was carried out with twenty one (21) students of the second year of the High School of a public state college of the North of Paraná, Brazil. The results emphasize that the majority of the students present meaningful signs of learning after applying the previous organizer, because the integration of new ideas to the concepts they already knew, as well as the ability to differentiate the new ideas existing in their cognitive structure.